Use of Ethnobotanical Data in the Search for and Identification of Potential Drug Plants. (The East and Central African Journal of Pharmaceutical Sciences, 2018)
Traditional medicine has utilized plants to palliate, cure and/or prevent diseases in both humans and animals. The acquisition of knowledge has been through trial and error, and observation. Today, the enhanced search for botanical drugs throughout the world has increased the need for accurate means of identifying plants with possible pharmacological and biological activity. A number of methodologies have been used in selecting plants likely to possess pharmacological properties, but many have recorded low success rates. Data reported in this paper reveal that the accuracy of identification of these herbal drugs for pertinent ailments using ethnobotanical data is almost as accurate as techniques applied in modern medical practice. This paper discusses the value of ethno-botanical data in the preliminary search for potential drug plants
Keywords: Ocimum; Plectranthus; ethnobotany; medicinal plants